2018
DOI: 10.1111/jth.14129
|View full text |Cite
|
Sign up to set email alerts
|

Combination of isocitrate dehydrogenase 1 (IDH1) mutation and podoplanin expression in brain tumors identifies patients at high or low risk of venous thromboembolism

Abstract: Essentials Risk stratification for venous thromboembolism (VTE) in patients with brain tumors is challenging.Patients with IDH1 wildtype and high podoplanin expression have a 6‐month VTE risk of 18.2%.Patients with IDH1 mutation and no podoplanin expression have a 6‐month VTE risk of 0%. IDH1 mutation and podoplanin overexpression in primary brain tumors appear to be exclusive. SummaryBackgroundVenous thromboembolism (VTE) is a frequent complication in primary brain tumor patients. Independent studies reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 24 publications
3
26
0
2
Order By: Relevance
“…The inverse association of CCL3 with VTE in our study was independent of previously described VTE risk factors in brain tumors [19][20][21][22][23]. For example, a higher glioma grade as well as distinct local tumor characteristics, such as the upregulation of podoplanin expression on tumor cells, are associated with a higher VTE risk [19].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The inverse association of CCL3 with VTE in our study was independent of previously described VTE risk factors in brain tumors [19][20][21][22][23]. For example, a higher glioma grade as well as distinct local tumor characteristics, such as the upregulation of podoplanin expression on tumor cells, are associated with a higher VTE risk [19].…”
Section: Discussionsupporting
confidence: 73%
“…For example, a higher glioma grade as well as distinct local tumor characteristics, such as the upregulation of podoplanin expression on tumor cells, are associated with a higher VTE risk [19]. Furthermore, an IDH1 wildtype status is linked to a higher risk of VTE, while patients with an IDH1 mutation have a very low VTE risk [20,21]. In addition, laboratory parameters, such as a low platelet count, a high leukocyte count and higher soluble P-selectin and D-Dimer levels, have been reported to be associated with a higher VTE risk in a larger cohort of patients with glioma [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IDH1 mutant tumors exhibited low level of TF immunostaining, and their corresponding levels of EV-associated TF activity (TF-MPs) in blood showed a tendency toward reduction, relative to the IDH wild-type disease. 56 In another subsequent study, it was found that combined low PDPN and IDH1 mutation signify the lowest VTE risk among all GBM patients, 90 even though PDPN is likely downregulated by mutant IDH1 at the level of the epigenome. 4,40 The molecular landscapes of pediatric brain tumors are vastly different than those in adults and are increasingly well characterized, 78,[91][92][93] but they are infrequently discussed in the context of CAT.…”
Section: Oncogenic Events and Brain Tumor Coagulomementioning
confidence: 97%